坤中高中一年级学生平翘舌音 “z, c, s, zh, ch, sh及r”的偏误分析 - Darwis Darwis; Lily Thamrin; Lusi Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2017)
AbstractChinese Hanyu Pinyin learning is a crucial step during the Chinese language learning. Indonesian students learning Hanyu Pinyin pronunciation would be affected by the Indonesian mother tongue ,and can meet with different kinds of difficulties,  especially the pronunciation of  the Blade-alveolars  z, c, s, and the Retro flexes zh, ch, sh, r. In view of the above, we madea survey on the Blade-alveolars  z, c, s, and the Retro flexes zh, ch, sh, r,among the students from the Pontianak middle  school of  Indonesia.  In the essay, we use the method of experimental research and  statistical analysis to analyze  the Chinese letter   z, c, s, and zh, ch, sh, r. In the research result, the students whose mother tongue is Indonesian will be affected by their mother tongue during pronouncing  the Chinese letter z, c, s, and zh, ch, sh, r. As a Chinese teacher teaching in Indonesia ,we should practice more and find more methods in the process of  teaching the Hanyu Pinyin, and  strengthen the using of it.And  I wish the essay can help during the study of Chinse whose mother tongue is Indonesia.                                                                                       Keywords: Chinese initials, Blade-alveolars, Retro-flexes, Experimental research method